Intra-specific foraging dynamics reveal anthropogenic impact on harbour seals (Phoca vitulina) in the Danish Kattegat and the German Wadden Sea - Lehnert, Kristina; Bethune, Elehna; Schulz-Kornas, Ellen; Siebert, Ursula; Kaiser, Thomas M. (Frontiers in Marine Science, 2025)
IntroductionMarine mammals are apex predators in the marine environment and seals are known as opportunistic hunters which adapt to prey availability in their distribution range. Knowledge about harbour seal diet is a crucial baseline parameter to assess environmental change in marine ecosystems, however inferring diet composition in marine animals remains challenging. The harbour seal subpopulations in the German North Sea and Danish Kattegat region underwent strong population dynamics during the last centuries. In the 1960s/70s they had undergone declines due to hunting pressure and pollutant exposure and experienced mass mortalities caused by virus epidemics in 1988. The hunting bans and conservation measures implemented since then in different areas may have altered the dietary preferences and foraging ecology of harbour seal populations in the Danish Kattegat and the German Wadden.MethodsIn this study the tooth abrasion in harbour seals from two geographic regions is investigated to infer on their foraging ecology by taking advantage of dental microwear texture analysis (DMTA) in archived museum specimens. The upper dentition of 82 harbour seals originating from seal skulls collected during 1988 (German Wadden Sea) and the 1970/80s (Danish Kattegat) in museum archives were analysed using DMTA to infer dietary abrasiveness.ResultsSignificant differences in dental microwear textures (DMT) between the Wadden Sea and Kattegat harbour seal groups were revealed. Danish Kattegat female harbour seals, and to a smaller extent Kattegat males, around the island of Hesselø displayed the roughest DMT reflecting a significantly higher intake of abrasives compared to the Wadden Sea harbour seals. The lack of significant DMT differences within the Hesselø subpopulation and the high variability of DMT in Hesselø females suggest a more generalistic foraging strategy as a response to high intra-specific competition in the protected area surrounding Hesselø.DiscussionThe slightly shifted DMT within Wadden Sea seals might be linked to a sexual segregation of foraging strategies in a larger, more resourceful North Sea habitat. DMTA is useful to reveal intra-specific foraging strategies in museum specimens from the past and different geographic regions. The novel technique opens new options to infer foraging dynamics in wildlife populations, taking advantage of valuable skeletal material from historic specimens in natural history collections, and offers new perspectives for non-invasive texture measurements on the dentition of live aquatic mammals. Information about foraging ecology of seal species related to anthropogenic stress in the past can inform current conservation and management in the face of environmental change.